Comparison of R&D innovation indicators of the visegrád group - Vukoszavlyev, Szlobodan (International Journal of Engineering and Management Sciences, 2019)
Innovation is a crucial strategic issue not only for businesses to maintain and improve competitiveness, but also has paramount role at a macroeconomic level how a national economy is able to contribute to the national division of labour. Innovation and research and development are particular and even more crucial in post-socialist countries which are trying to catch up with Western Europe in an economic point of view. We compared countries in the Visegrád Group in the study regarding their innovation indexes, R&D indicators and corporate innovations. These indicate that countries in the Visegrád Group are lagging behind the European Union. The Czech Republic ranks the first place in almost each aspect among the countries in the Visegrád Group. As for time series indicators, there is a steadily improving tendency in R&D. Regarding measuring innovation and R&D, it can be concluded that perfect method and scorecard are not available, indexes based on varying methods may generate different results and decision taking only one index into consideration cannot be made in business practice. In my opinion, R&D indicators are dominant to a large extent in comprehensive innovation indexes that might be misleading in the assessment of innovation (particularly in corporate innovation).